Implementasi Kebijakan Alih Fungsi Lahan Pertanian ke Non-Pertanian di Sleman berdasarkan Perspektif Institusionalis - Wahidatul Rizqi (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2020)
The increasing population in urban areas results in higher land demand but reduced land capacity. Sleman is an area that experienced a decrease in land quality due to the conversion of agricultural land to settlements. The high rate of land use change which is increasingly spreading has resulted in the government having to intervene in dealing with the problem with the policy of land conversion. However, the reality of the policy is that it has not been able to resolve public problems which are considered to be just formalities. This paper tries to discuss what context and content are capable of influencing land use change policies in sleman with institutionalist perspectives in accordance with Regional Regulation No. 12/2012 on Regional Spatial Planning (RTRW). The results of this paper that the implementation of policies for the conversion of agricultural land to non-agriculture in Sleman in the Institutionalist perspective there are two things that affect the content and policy context. The content is the party whose interests are affected, the types of benefits that can be obtained, the range of changes that can be expected, the position of decision makers, program implementers, and the resources that can be provided. While the context is the power, interests and strategies of the actors involved